Retrospective study on the effect of Ademetionine 1, 4-Butanedisulfonate for intravenous injection on peripheral superficial veins (静脉注射丁二磺酸腺苷蛋氨酸对外周浅静脉影响的回顾性研究) - SHEN Nian (沈念); QIN Jingxia (覃静霞) (Journal of International Translational Medicine Limited, 2024)
Objective In order to understand the effect of intravenously injected Ademetionine 1, 4-Butanedisulfonate (Transmetil) on peripheral superficial veins, and to provide scientific basis for rational treatment of phlebitis caused by intravenously injected Transmetil. Combined with the mechanism and causes of phlebitis, the corresponding treatment methods and nursing measures were put forward to prevent and alleviate the related symptoms of phlebitis. Methods An retrospective study was conducted. A total of 163 patients admitted to the Department of Interventional Radiology, Yichang Central People's Hospital from January 1, 2023 to December 31, 2023 were selected as the study subjects, of which 61 patients were treated with indwelling needle intravenous infusion of Transmetil according to the drug instructions as the experimental group, and 102 patients received intravenous infusion of isotonic fluid with indwelling needles as the control group. Investigations were conducted using the pharmacological properties of Transmetil, the causes and mechanisms of phlebitis, and the types and grades of phlebitis. Pain, skin redness and swelling range, rope-like inelastic length of vein and phlebitis grade are the main observation objects. Results In strict accordance with the instructions of the configuration method and infusion speed operation using indwelling needle intravenous infusion of Transmetil, peripheral superficial veins can develop phlebitis. The occurrence of phlebitis is mainly seen in the red swelling type and indurated type(χ²=8. 69, P＜0. 05), among which phlebitis can be seen in grade 1, grade 2, grade 3, among which grade 3 is more common(χ²=116. 22, P＜0. 01), and its pain is mainly 2 and 3 points(χ²=85. 12, P＜0. 01). Conclusion Intravenous injection of Transmetil can cause phlebitis in peripheral superficial veins. (目的 了解静脉注射注射用丁二磺酸腺苷蛋氨酸(思美泰)对外周浅表静脉的影响, 为合理治疗因静脉注射思美泰而产生的静脉炎而提供科学依据。结合静脉炎的产生机制及原因提出相应的处理方法及护理措施, 预防及减轻静脉炎的相关症状。方法 采用回顾性研究方法, 抽取2023年1月1日-2023年12月31日就诊于宜昌市中心人民医院介入放射科的163名患者作为研究对象, 其中61名患者采用留置针依照药品说明书静脉输注思美泰作为试验组, 102名患者采用留置针静脉输注等渗性液体作为对照组。利用思美泰的药理特性、产生静脉炎的原因及机制、静脉炎的分型和分级等专业知识进行调查研究, 主要观察疼痛、皮肤红肿范围、静脉呈条索状无弹性的长度及静脉炎级别等指标。结果 在严格按照说明书的配置方法及输液速度进行操作采用留置针静脉输注思美泰时外周浅表静脉可发生静脉炎。发生的静脉炎主要见于红肿型和硬结型(χ²=8. 69, P＜0. 05), 其中静脉炎可见于1级、2级、3级其中以3级多见(χ²=116. 22, P＜0. 01), 其产生的疼痛以2分和3分为主(χ²=85. 12, P＜0. 01)。结论 静脉注射思美泰可导致外周浅表静脉发生静脉炎。)